Introduction à la dette écologique en droit international : dette négative et dette positive - Noémie Candiago (VertigO)
The ecological debt is a political concept which seeks to expose the harmfulness of the production and consumption patterns based on the extraction of natural resources and their exchange in a market-driven economy. It is often reduced to a financial liability for the industrialized countries involved. Yet, this only corresponds to one side of the ecological debt. If repairing is a fundamental function of the law, the latter must also set out positive rules, in this case about the sustainable management of natural resources. This article presents the different approaches of ecological debt and then should highlight its constituent side by introducing the primary norms representative of the logic of the ecological debt.